Pendekatan Transpersonal pada Proses Diagnostik: Memahami Dimensi Spiritual dalam Asesmen Psikologis - Maharani Eka; Konto Iskandar Dinata (Al-Kindi, 2026)
The transpersonal approach in diagnostic processes offers a holistic perspective that incorporates the spiritual dimension as an essential component in understanding an individual’s psychological condition. This study aims to examine the application of the transpersonal approach in psychological assessment and explore how spiritual dimensions influence diagnostic outcomes. Through theoretical analysis and a review of relevant literature, the study finds that spiritual experiences, religious values, and the search for life meaning often play a significant role in shaping emotional and behavioral responses. Integrating transpersonal aspects enables psychologists to distinguish between healthy spiritual experiences and psychopathological symptoms, thereby reducing the risk of misdiagnosis. Moreover, this approach promotes a more humane and culturally sensitive assessment process that aligns with the client’s spiritual background. The findings demonstrate that understanding spiritual dimensions not only enriches diagnostic accuracy but also enhances the effectiveness and meaningfulness of psychological interventions. Therefore, the transpersonal approach is crucial in modern assessment practices, particularly within culturally and religiously diverse communities.